2021
DOI: 10.3390/ijms22031204
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Activity of Endocannabinoid-Hydrolyzing Enzymes MAGL and FAAH in Key Regions of Peripheral and Central Nervous System Implicated in Migraine

Abstract: In migraine pain, cannabis has a promising analgesic action, which, however, is associated with side psychotropic effects. To overcome these adverse effects of exogenous cannabinoids, we propose migraine pain relief via activation of the endogenous cannabinoid system (ECS) by inhibiting enzymes degrading endocannabinoids. To provide a functional platform for such purpose in the peripheral and central parts of the rat nociceptive system relevant to migraine, we measured by activity-based protein profiling (ABPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 79 publications
4
19
1
Order By: Relevance
“…Inhibition of FAAH activity by URB597 resulted in an increase in AEA and CB1 receptor levels, as well as a decrease in CB2 receptor expression. Interestingly, 2-AG was less effective in our experiments despite the fact that it is present in higher concentrations in the brain than AEA and can induce stimulation equally through CB1 and CB2 receptors [58]. It may be due to lower levels of 2-AG access to the presynaptic CB1 receptors, as well as to the fact that the 2-AG-degrading enzyme is closer to the target of the CB1R than AEA.…”
Section: Discussionmentioning
confidence: 54%
“…Inhibition of FAAH activity by URB597 resulted in an increase in AEA and CB1 receptor levels, as well as a decrease in CB2 receptor expression. Interestingly, 2-AG was less effective in our experiments despite the fact that it is present in higher concentrations in the brain than AEA and can induce stimulation equally through CB1 and CB2 receptors [58]. It may be due to lower levels of 2-AG access to the presynaptic CB1 receptors, as well as to the fact that the 2-AG-degrading enzyme is closer to the target of the CB1R than AEA.…”
Section: Discussionmentioning
confidence: 54%
“…A certain limitation of our study is that it is a narrative review and not a systematic one, but considering the aforementioned limits of the studies found (the small sample sizes, the lack of placebo-controlled studies, the often-retrospective design, the different titrations of cannabinoid preparations and the different routes of administration), the results of a systematic review would not have been too dissimilar from a narrative one. The adverse events linked to the modulation of the ECS, increasing eCBs, are still uncertain and should be properly assessed, because, although some authors believe it may be a relatively safe option [ 59 ], a recent clinical trial with a FAAH inhibitor (in this case, not used for migraine) was interrupted as a result of serious adverse events [ 60 ]. In conclusion, promising data are emerging on the possible role of ECS in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Direct microinjections of cannabinoid agonists into the PAG induce antinociception (Lichtman et al 1996, Martin et al 1995, Wilson et al 2008, Wilson-Poe et al 2013) through activation of CB1Rs that inhibit GABA release in the PAG (Vaughan et al 2000). Recent work has highlighted MAGL inhibitors as analgesic therapeutic options (Anderson et al 2014, Curry et al 2018, Della Pietra et al 2021, Diester et al 2021, Ignatowska-Jankowska et al 2015) but the data presented here suggest that MAGL inhibition may not be a viable strategy if inflammation impairs MAGL function and desensitizes CB1Rs. However, systemic administration of MAGL inhibitors, as well as fatty acid hydrolase (FAAH) inhibitors and combinations of the two, increase levels of the eCBs 2-AG and anadamide and result in anti-hyperalgesia in both neuropathic and inflammatory pain models (Anderson et al 2014, Jayamanne et al 2006, Mitchell et al 2005).…”
Section: Discussionmentioning
confidence: 79%